Attaining Business Sustainability by Building the Organization Health Index in Organization Behavior: Case Study in Indonesia Private Clinical Laboratory - Rachmasari, Ratih; Sukoco, Badri Munir (Jurnal Manajemen, 2019)
Indonesian health industry predicted will rapidly develop in the next five years. Indonesia health spending spending will reach US $ 60.6 billion over the period 2012-2018. PT. X, a company in the health industry, has significant growth and widely spread 18 branches all over Indonesia. Therefore, the business sustainability of PT. X needs to be continuously maintained and improved. In accordance with the company's vision "became a national referral center clinical laboratory”, keeping a good performance as well as business sustainability, PT. X need to maintain a company performance and health of their organization. A questionnaire referring to nine element McKinsey Organizational Health Index was applied to assess PT.X organization health. The OHI score obtained from the survey shows that PT X is quite healthy due to surpass the threshold of a healthy organization. It is recommended that organizational behaviour improvement refers to market focus basic model; achieving excellent performance for maintaining business sustainability.